1999
DOI: 10.1590/s0004-282x1999000600005
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis in Brazil: analysis of cerebrospinal fluid by standard methods

Abstract: -The demonstration of intrathecal IgG synthesis has been used as an important laboratory parameter to support the diagnosis of multiple sclerosis(MS). The Committee for European Concerted Action for Multiple Sclerosis has recommended a protocol for the assessment of intrathecal IgG synthesis. We applied this methodology to determine the cerebrospinal (CSF) profile of 128 Brazilian patients with MS. We detected hypercytosis lower than 35 cells/mm 3 in 97%, protein lower than 80mg/dl in 99%, normal blood-CSF bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
4
1
1
Order By: Relevance
“…This would seem to be in accordance with previous reports of the high numbers of non-white cases of Devic's syndrome in the United Kingdom, 14 the United States, 15 and Martinique. 12 There were important differences in the CSF findings between our ONM patients and those with definite MS: mild pleocytosis and increased CSF protein content were more common in ONM and increased IgG indices and oligoclonal bands, which occurred in 85% of the clinical definite MS Brazilian patients, 24 were very rare. Compared with MS where the CSF changes are independent of the activity of the disease, in ONM all the CSF abnormalities (pleocytosis, high level of protein, high IgG index, and oligoclonal bands) disappeared during remission in the majority of the cases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This would seem to be in accordance with previous reports of the high numbers of non-white cases of Devic's syndrome in the United Kingdom, 14 the United States, 15 and Martinique. 12 There were important differences in the CSF findings between our ONM patients and those with definite MS: mild pleocytosis and increased CSF protein content were more common in ONM and increased IgG indices and oligoclonal bands, which occurred in 85% of the clinical definite MS Brazilian patients, 24 were very rare. Compared with MS where the CSF changes are independent of the activity of the disease, in ONM all the CSF abnormalities (pleocytosis, high level of protein, high IgG index, and oligoclonal bands) disappeared during remission in the majority of the cases.…”
Section: Discussionmentioning
confidence: 81%
“…These data support the proposition that the majority of patients with Devic's syndrome should only rarely be included as cases of MS. 6 RNMO must be differentiated from relapsing remitting MS (RRMS) on the basis of demographic, clinical, MRI, and CSF features. Recent data from the South Atlantic Project, a Brazilian survey on MS confirm that Brazilian MS patients have clinical, MRI, CSF, and genetic data [23][24][25] that are quite similar to the "western type" of MS. Demographic data indicated that in Brazilians, a highly ethnically diversified population, the disease was most prevalent in young white women. RRMS was present in 89% and a primary progressive disease in 11%; the EDSS scores in the RRMS group showed mild disability in 70%, moderate in 9.8%, and severe in 19.9% of the patients after a mean duration of disease of seven years.…”
Section: Discussionmentioning
confidence: 95%
“…Ocorre um processo seletivo de inflamação local com desmielinização, envolvendo mecanismos imunes celular e humoral. Como consequência deste processo surgem as alterações no líquido cefalorraqueano (LCR) características da doença, tais como a presença de bandas IgG oligoclonais e aumento do índice de IgG, indicando a síntese intratecal de imunoglobulinas 1,2 . A maioria dos pacientes (85%) inicia o seu quadro clínico com a forma surto-remissão e, em cerca de 10 anos, evoluem para forma clínica crônica progressiva secundária.…”
unclassified
“…It contributes to the monitoring of inflammatory processes in the CNS. A Brazilian pioneering study showed the presence of CSF oligoclonal IgG bands in 85% of patients with definite MS 3 . However, it may found up to 95% of cases utilizing isoelectric focusing with IgG immunoblotting 2 .…”
mentioning
confidence: 99%
“…Therefore, the test has a high predictive negative value. It does not represent a disease marker, considering that it is not specific for MS, since it may be found in other neurological disorders of the CNS [2][3][4] . Demonstration of oligoclonal IgG bands locally synthesized has been used more recently for the MS prognostic evaluation.…”
mentioning
confidence: 99%